Application strategy of finite element analysis in artificial knee arthroplasty - Zhang, Zi-Heng; Qi, Yan-Song; Wei, Bao-Gang; Bao, Hu-Ri-Cha; Xu, Yong-Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
As the most effective method for the treatment of end-stage knee osteoarthritis, artificial knee arthroplasty is widely used in the field of joint surgery. At present, finite element analysis has been used in orthopedic biomechanical research. We believe that in the process of total knee arthroplasty, the mobile-plateau system reduces the contact surface stress of the tibial-femoral joint compared with the fixed-plateau system, thus reducing the wear of the polyethylene insert; compared with the mechanical alignment, the maximum stress and maximum strain of the femoral prosthesis and polyethylene insert of the TKA with motion alignment are reduced, and the stress is lower, so as to reduce the wear of the joint contact surface and prolong the life of the prosthesis. In the process of UKA, the femoral and tibial prostheses of the movable plateau are in better formability, which can reduce the wear of the prosthesis, while the UKA of the fixed plateau should avoid the local stress concentration caused by excessive fitting and lead to accelerated wear of the prosthesis. in RTKA, the design length of the extension stem should maintain the best balance between preserving bone and reducing stress around the prosthesis after implantation. Compared with the cemented stems implant, the press-fit stem implant shows higher fretting. Finally, compared with the traditional mechanical research, the finite element analysis can simulate the knee joint relatively accurately, which makes up for the deficiency of the traditional mechanics in the knee joint research.